Regulatory Framework and Research: A Review of IPO Research Conducted in the U.S., China, and India - Jain, Neeta (Indian Journal of Finance, 2013)
Although the area of research is the same, i.e. IPO underpricing, however, there are many apparent differences between the methods of research, focus of the research , amount of the research, and the findings of the research across countries and time periods. These differences become wide if compared between the U.S., China, and India. In the U.S., the focus of IPO research has been on the role of the underwriters and discretionary power of share allocation. While in China, the focus is on the effect of frequently changed regulatory framework on IPO underpricing. In India, it can be seen that most of the studies are based on the publicly available information, considering IPO firm's and the issue's characteristics as the main study variables. The present study aims to review the literature of IPOs in the U.S., China, and India. The major differences in the methods of pricing and other related regulations should be the major concerns while applying the IPO market models across countries. The present review study covers the time period from 1970s to 2012.